PENGUKURAN KUALITAS LAYANAN SISTEM INFORMASI MENGGUNAKAN SERVQUAL METHODE - Sahfitri, Vivi (Universitas Bina Darma, 2014)
Implementation of information systems is one of the supporting facilities for the performance of an institution . Utilization Information System aims to simplify the task of the user in order to achieve savings in time, cost , and resource decision-making. User Satisfaction of an information system is one of the factors or measures of success for the development and implementation of Information Systems. This study analyzed the use of Information Systems service quality variables contained in the method of the Service Quality. The results of this study indicate that simultaneous or partially simultaneous or there is a significant and positive relationship between the variables in the study variables . While the regression analysis of the results obtained by the fact that the contribution of the five variables is 66.5 % of the variable User Satisfaction Information System.